The C9orf72 protein interacts with Rab1a and the ULK1 complex to regulate initiation of autophagy. (22nd June 2016) - Webster, Christopher P; Smith, Emma F; Bauer, Claudia S; Moller, Annekathrin; Hautbergue, Guillaume M; Ferraiuolo, Laura; Myszczynska, Monika A; Higginbottom, Adrian; Walsh, Matthew J; Whitworth, Alexander J; Kaspar, Brian K; Meyer, Kathrin; et al.
Abstract: A GGGGCC hexanucleotide repeat expansion in the C9orf72 gene is the most common genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia (C9ALS/FTD). C9orf72 encodes two C9orf72 protein isoforms of unclear function. Reduced levels of C9orf72 expression have been reported in C9ALS/FTD patients, and although C9orf72 haploinsufficiency has been proposed to contribute to C9ALS/FTD, its significance is not yet clear. Here, we report that C9orf72 interacts with Rab1a and the Unc‐51‐like kinase 1 (ULK1) autophagy initiation complex. As a Rab1a effector, C9orf72 controls initiation of autophagy by regulating the Rab1a‐dependent trafficking of the ULK1 autophagy initiation complex to the phagophore. Accordingly, reduction of C9orf72 expression in cell lines and primary neurons attenuated autophagy and caused accumulation of p62‐positive puncta reminiscent of the p62 pathology observed in C9ALS/FTD patients. Finally, basal levels of autophagy were markedly reduced in C9ALS/FTD patient‐derived iNeurons. Thus, our data identify C9orf72 as a novel Rab1a effector in the regulation of autophagy and indicate that C9orf72 haploinsufficiency and associated reductions in autophagy might be the underlying cause of C9ALS/FTD‐associated p62 pathology. Synopsis: C9ALS/FTD‐associated C9orf72 is a Rab1a effector that controls initiation of autophagy by regulating ULK1 complex trafficking. Disruption of C9orf72 function inhibits autophagy and mimics the p62 pathology found in C9ALS/FTD patients. C9ALS/FTD iNeurons display reduced autophagy. C9orf72 regulates ULK1 complex‐dependent initiation of autophagy. C9orf72 is a Rab1a effector that controls trafficking of the ULK1 complex. C9orf72 deficiency inhibits autophagy and mimics C9ALS/FTD p62 pathology. C9ALS/FTD patient‐derived iNeurons display reduced autophagy. Abstract : ALS/FTD‐associated C9orf72 is a Rab1a effector that controls initiation of autophagy by regulating ULK1 complex trafficking.